Psychopathology history, diagnosis, and empirical foundations - Craighead, W. Edward (John Wiley & Sons, Inc., 2013)
"Designed for graduate level courses in adult psychopathology, the Second Edition of this book incorporates the newly released (2013) DSM-5 . Unique in its approach, this text presents a historical context in which current diagnoses are made. Presenting an overview of the issues and methodologies of conducting assessments, each of the major psychological disorders is discussed in a standard format in the chapter dealing with that disorder. The text includes new chapters on nonalcohol substance abuse and contextual factors affecting diagnoses. Each chapter covers: description from DSM, using case examples; epidemiology; basic research, including neurobiology and neuroscience of the disorder; prevalence and consequences of the disorder; behavioral, social, cognitive, and emotional aspects of the disorder; and treatment of the disorder, using clinical examples showing how psychopathology and assessment influence treatment"--